Perlakuan Benih Menggunakan Rizobakteri Pemacu Pertumbuhan terhadap Pertumbuhan Vegetatif dan Hasil Tanaman Cabai Merah (Capsicum annuum L.) - Mardiah Mardiah; Syamsuddin Syamsuddin; Efendi Efendi (Jurnal Floratek, 2016)
Seed Treatment Using Rhizobactery Growth Promoters to Vegetative Growth and Yield of Red Chili Plant (Capsicum annum, L.) ABSTRACT. This research aims to determine the effect of seed treatment using plant growth promoter rhizobactery to vegetative growth and yield of two varieties of red chili in the field. The experiment using factorial randomized block design. Factors under study consists of varieties chili PM888 and PM999. Meanwhile, type of rhizobactery consists of Bacillus lichiniformis, Necercia sp., Actinobacter sp., Bacillus larvae, and Pseudomonas capacia. Seed as control is not treated with rhizobactery. Each treatment combination was replicated 3 times. Each experimental unit represented by 5 sample plants. Observed parameters comprise of vegetative growth and reproductive parameters. Result data from observation were analyzed using ANOVA, followed by different test between treatment with Honestly Significant Difference test on the significant level α = 0,05. The results showed that PM888 variety is superior compared with PM999 respect to the response of these varieties for seed treatment with rhizobactery based on the evaluation of the parameters of vegetative growth. While based on production parameters, the number of fruit per plant, PM888 variety significantly more fruit if seed treated using rhizobactery isolate of P. capacia . Meanwhile, rhizobactery species that effectively increase the number of fruit per plant in PM999 variety is P.capacia and P. dimuta. Result of weight measurement of fruit per plant showed that almost all rhizobacteries which effectively increase weight of fruit per plant PM888 variety, except rhizobactery of species Actinobacter sp. As for PM999 variety, there are 4 species rhizobactery which effectively increase the weight of fruit per plant, namely P. capacia , P. dimuta , Necercia sp , and Flavobacterium sp.